Green Hydrogen in Europe: Do Strategies Meet Expectations? - André Wolf; Nils Zander (Intereconomics, 2021)
Against the backdrop of the EU's more ambitious climate targets, the technology of green hydrogen production has gained increasing importance in national plans to implement the energy transition.
Keywords: 330